Echoes from Labor's Wars: The Expanded Edition - Frager, Ruth A. (Labour / Le Travail, 1993)
The article reviews the book, "Echoes from Labor's Wars: The Expanded Edition," by Dawn Fraser,

Sweatshop Strife: Class, Ethnicity, and Gender in the Jewish Labour Movement of Toronto, 1900-1939 - Frager, Ruth A. (Social history of Canada, 1992)
In the first half of the twentieth century, many of Toronto's immigrant Jews eked out a living in the needle-trade sweatshops of Spadina Avenue. In response to their expliotation on the shop floor, immigrant Jewish garment workers built one of the most advanced sections of the Canadian and American labour movements. Much more than a collective bargaining agency, Toronto's Jewish labour movement had a distinctly socialist orientation and grew out of a vibrant Jewish working-class culture. Ruth Frager examines the development of this unique movement, its sources of strength, and its limitations, focusing particularly on the complex interplay of class, ethnic, and gender interests and identities in the history of the movement. She examines the relationships between Jewish workers and Jewish manufacturers as well as relations between Jewish and non-Jewish workers and male and female workers in the city's clothing industry. In its prime, Toronto's Jewish labour movement struggled not only to improve hard sweatshop condistions but also to bring about a fundamental socialist transformation. It was an uphill battle. Drastic economic downturns, hard employer offensives, and state repressions all worked against unionists' workplace demands. Ethnic, gender, and ideological divisions weakened the movement and were manipulated by employers and their allies. Drawing on her knowledge of Yiddish, Frager has been able to gain access to original records that shed new light on an important chapter in Canadian ethnic, labour, and women's history. --Publisher's description
Keywords: History; Jewish labor unions; Jews; Labor movement; Ontario Toronto; WOMEN in the labor movement

The World of Our Mothers: The Lives of Jewish Immigrant Women - Frager, Ruth A. (Labour / Le Travail, 1990)
The article reviews the book, "The World of Our Mothers: The Lives of Jewish Immigrant Women," by Sydney Stahl Weinberg.
Keywords: JEWISH women; Nonfiction; REVIEWS; WEINBERG, Sydney Stahl; WORLD of Our Mothers: The Lives of Jewish Immigrant Women, The (Book); books

Joe Salsberg: A Life of Commitment - Frager, Ruth A. (Labour / Le Travail, 2015)
This article reviews the book, "Joe Salsberg: A Life of Commitment," by Gerald Tulchinsky.

Labour History and the Interlocking Hierarchies of Class, Ethnicity, and Gender: A Canadian Perspective - Frager, Ruth A. (International Review of Social History, 1999)
This paper develops the concept of interlocking hierarchies [within the working class] by focusing on the Canadian situation. While emphasizing the complex dynamics of worker resistance and adaptation, the paper briefly examines the shortcomings of Canadian working-class historiography. The paper then explores the significance of interlocking hierarchies and sketches the ways in which this analytical framework can be applied, first by emphasizing gender issues and secondly by emphasizing ethnicity in the Canadian context, particularly in the late nineteenth and early twentieth centuries. (I use the term ‘‘ethnicity’’ broadly in order to avoid using the term ‘‘race’’ as much as possible, so as not to lend credence to the notion that ‘‘race’’ represents a fixed biological category.) In emphasizing ethnicity, the paper focuses first on issues concerning immigrant workers from Asia and then on issues concerning immigrant workers from southern and eastern Europe. --From author's introduction

Discounted Labour: Women Workers in Canada, 1870-1939 - Frager, Ruth A.; Patrias, Carmela (Themes in Canadian history, 2005)
The years between 1870 and 1939 were a crucial period in the growth of industrial capitalism in Canada, as well as a time when many women joined the paid workforce. Yet despite the increase in employment, women faced a difficult struggle in gaining fair remuneration for their work and in gaining access to better jobs. Discounted Labour analyses the historical roots of women's persistent inequality in the paid labour force. Ruth A. Frager and Carmela K. Patrias analyse how and why women became confined to low-wage jobs, why their work was deemed less valuable than men's work, why many women lacked training, job experience, and union membership, and under what circumstances women resisted their subordination. Distinctive earning discrepancies and employment patterns have always characterized women's place in the workforce whether they have been in low-status, unskilled jobs, or in higher positions. For this reason, Frager and Patrias focus not only on women wage-earners but on women as salaried workers as well. They also analyze the divisions among women, examining how class and ethnic or racial differences have intersected with those of gender. Discounted Labour is an essential new work for anyone interested in the historical struggle for gender equality in Canada. --Publisher's description
Keywords: 19th century; 20th century; Canada; Employment; History; Sexual division of labor; Women

Union Sisters: Women in the Labour Movement - Briskin, Linda; Yanz, Lynda; Adams, Jane; Attenborough, Susan; Colley, Susan; Cumsille, Alejandra; Darcy, Judy; David, Françoise; David, Hélène; Egan, Carolyn; Epstein, Rachel; Field, Debbie; et al. (Women's Press, 1985)
Women's activism in unions has increased dramatically in the last decade, creating a sense of renewed vitality and excitement in the trade union movement. Union Sisters is a attempt to document the struggles and victories of the movement of union women as well as to provide some direction to women and unions as they fight to defend the interests of working people. --Introduction